The Impact of russia's Military Aggression on the Formation of Macroeconomic Indicators of Post-Soviet Countries and Support for Ukraine - Antonina Tomashevska; Andrii Pelekhatyi (Vasyl Stefanyk Precarpathian National University, 2023)
The economic consequences of the war in Ukraine are felt all over the world. Russian aggression has put pressure on global commodity prices, exacerbated disruptions in supply chains, and fueled inflation in most countries around the world. The countries that have decided to support russia today, or are trying to avoid confrontation with them, should be clearly aware that in the eyes of Ukrainians and the whole world they are silent accomplices in crimes and genocide against the Ukrainian people. The purpose of the article is to analyze how the countries of the former USSR reacted to the russian aggression against Ukraine, the statements of politicians and the decisions of the governments of the countries that, together with Ukraine, were part of the USSR until 1991; to determine how Westernization affects macroeconomic indicators and the formation of European values in the countries of the post-Soviet space. The article defines aspects of the formation of macroeconomic factors in the countries of the post-Soviet space. It was determined that despite the right of the union republics to state sovereignty formally enshrined in the Constitution, the USSR was actually a unitary state. It was created as a highly centralized, totalitarian and authoritarian system, incompatible with the principles of democracy, free and full development of nations. The study analyzes when the whole world expresses support and help to Ukrainians, at the same time, some post-Soviet countries, in particular, the leader of Kyrgyzstan, expressed support to the Russian president. Another ally in russia's war against Ukraine is Tajikistan. The main components of the economic factor of Westernization are considered: GDP per capita, capital investments and the size of the minimum wage. To calculate the extent to which groups of post-Soviet states are related in the studied macroeconomic indicators, we calculated the coefficient of variation based on the standard deviation.